2001
DOI: 10.1111/j.1095-8649.2001.tb00564.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of environmental hypercapnia on pulmonary ventilation of the South American lungfish

Abstract: Aquatic hypercapnia at PCO 2 of 55 mmHg significantly increased pulmonary ventilation in the South American lungfish Lepidosiren paradoxa, whereas no significant increases occurred when hypercapnia was applied to the gas phase with or without concomitant aquatic hypercapnia. On return from gas phase hypercapnia to inspiration of air there was a marked transient increase of ventilation. This post-hypercapnic response is discussed in relation to the possible presence of upper airway or pulmonary CO 2 receptors t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…When water PCO 2 rose from 0 to 20 mmHg, this species increased respiratory frequency of pulmonary ventilation 2-fold from about 12 to 24 breaths/hr (Johansen and Lenfant,'68). Likewise, Lepidosiren increased pulmonary ventilation in response to higher water CO 2 levels (Sanchez and Glass, 2001), indicating a similar respiratory control in the two species.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…When water PCO 2 rose from 0 to 20 mmHg, this species increased respiratory frequency of pulmonary ventilation 2-fold from about 12 to 24 breaths/hr (Johansen and Lenfant,'68). Likewise, Lepidosiren increased pulmonary ventilation in response to higher water CO 2 levels (Sanchez and Glass, 2001), indicating a similar respiratory control in the two species.…”
Section: Discussionmentioning
confidence: 96%
“…Once again, this indicates that lungfish share various features of pulmonary ventilatory control with the tetrapods. Recently, Sanchez and Glass (2001) reported that Lepidosiren exhibits "post-hypercapnic hyperpnea." When combined with aquatic hypercapnia, inspiration of hypercapnic gases into the lungs slightly increased pulmonary ventilation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In tropical aquaculture ponds with high stocking density, no aeration and little water exchange, CO 2 is likely to reach high levels because air-breathing fishes typically obtain oxygen from the air breathing organ, but excrete CO 2 across their gills into the water (Evans et al, 2005;De Lima Boijink et al, 2010). One exception may be L. paradoxa which appears to increase lung rather than gill ventilation during exposure to hypercapnia (Sanchez & Glass, 2001). In many tropical areas, water is rather poorly buffered and the putatively high CO 2 level would therefore cause considerable reductions in water pH.…”
Section: A R B O N D I Ox I D Ementioning
confidence: 99%
“…It has long been recognised that fish exhibit pronounced physiological responses, including hyperventilation and catecholamine release, when exposed to environmental hypercarbia (see review by Perry and Wood,'89); more recently, the cardiovascular responses to hypercarbia have been characterised. Species from several major groups have been studied including representatives from the Chondrichthyes (Randall et al,'76;Heisler et al,'88;Graham et al,'90), Chondrostei (Crocker et al, 2000), Lepisosteidae (Smatresk and Cameron,'82), Dipnoi (Sanchez and Glass, 2001), and Teleostei (Janssen and Randall, '75;Burleson and Smatresk, 2000;Reid et al, 2000;Soncini and Glass, 2000;Sundin et al, 2000;Perry and McKendry, 2001). Until recently, it was generally accepted that the physiological responses to hypercarbia were not directly attributable to changes in CO 2 /pH but instead were an indirect effect of the marked Bohr and Root effects that occur during hypercapnic acidosis.…”
Section: Co 2 Chemoreceptionmentioning
confidence: 99%